Gulbenkian Think Tank on Water and the Future of Humanity (2014). Water and the Future of Humanity. Revisiting Water Security. New York: Springer: 241 pp. - Brito, Brígida (2014)
Within the framework of the International Decade for "Water as source of life" (2005-15), the Think Tank of Foundation Calouste Gulbenkian (FCG) on Water and the Future of Humanity, published (joint edition by FCG and Springer) the book "Water and the Future of Humanity Revisiting Water Security" in early 2014. This book gathers the work and debate of eleven internationally acknowledged experts whose work has focuses on water resource management and community water policy.